1988
DOI: 10.1111/j.1365-2117.1988.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

The Corinth‐Patras rift as the initial stage of continental fragmentation behind an active island arc (Greece)

Abstract: During the migration of the back arc extension from central to western Greece the Corinth and Patras grabens are being formed. Orthogonal opening of these graben zones is accomplished by WNW listric normal faults and NNE transfer faults which produce an along-axis fragmentation. The listric faults show an increase in the dip of the fault plane westwards as well as a decrease in the maximum extension rate from 50% to the east in the Corinth graben, to 10% to the west in the Patras graben. Similarly, towards the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
43

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 29 publications
(7 reference statements)
1
70
0
43
Order By: Relevance
“…Numbers refer to sampling locations. Lithofacies after Loftus & Tsoflias (1971), Zelilidis et al (1988) and tectonic data after Doutsos et al, 1988. …”
Section: Methodsmentioning
confidence: 99%
“…Numbers refer to sampling locations. Lithofacies after Loftus & Tsoflias (1971), Zelilidis et al (1988) and tectonic data after Doutsos et al, 1988. …”
Section: Methodsmentioning
confidence: 99%
“…Regarding the faults and major discontinuities encountered in the area, the examination of air photos and the field work revealed that their distribution and orientation show a rather dispersion, but with domination of these with N70°-90°E and N30°-40°W azimuths that are the oldest ones and resulted from the general uplifting of the area, as well as of these with N40°-50°E, N70°-80°W and N10°-20°E azimuths, which are connected with the migration of the Aegean arch (Doutsos et al, 1988).…”
Section: Geological Settingmentioning
confidence: 99%
“…The geological and hydrogeological conditions of the landfill area are characterized by the presence of thick sequences of Plio-Pleistocene fine sediments (clayey marls, marls and siltstones) with lensoidal intercalation of sandstones and conglomerates, which do not sustain a considerable groundwater table (Zelilidis et al, 1998;Doutsos et al, 1988).…”
Section: The Sanitary Landfill Of Patrasmentioning
confidence: 99%